ลักษณะมุ่งอนาคตของนักเรียนชั้นมัธยมศึกษาตอนปลายในเขตอำเภอเมือง จังหวัดน่าน - สาวิตรี เต็งณฤทธิ์ศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this cross-sectional descriptive study were to examine future orientation of high school students in Amphoe Mueang, Nan Province. The samples were 394 students from 5 schools in Ampher Meung, Nan province which consisted of 137 males and 257 females with average age of 17.5 years old. The instruments were questionnaire on general demographic data, future orientation scale constructed by Supicha Krinbu-nga, Internal-External Locus of control scale constructed by Liverant, Rotter and Crown. All data were analyzed with the SPSS/FW program to determine percentage, mean, standard deviation, T-test, F-test (One-way ANOVA), Pearson s Product Moment Correlation Coefficient and Enter multiple regression analysis. The major findings were as followed: 1. The majority of high school students in Amphoe Mueang, Nan province have Future orientation score in moderate level. 2. Difference in gender, age, academic grades and GPA had statistically significant on Future orientation. 3. Gender, academic grades and GPA were statistically factors which could predict Future orientation at 9.7%. 4. Future orientation was positively related with age at .01 level of significance. 5. Future orientation was negatively related with Internal-External Locus of control at .01 level of significance.